2021
DOI: 10.1186/s42494-021-00059-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of the TNFα-mediated astrocyte signaling pathway in epilepsy

Abstract: Epilepsy is a common disease  in the central nervous system. There is growing evidence that epilepsy is associated with glial cells, including astrocytes. Tumor necrosis factor α (TNFα) is a “master regulator” of proinflammatory cytokine production and is secreted by microglia and astrocytes. TNFα secreted by microglia can activate astrocytes. Additionally, TNFα can regulate neuron activity and induce epilepsy by increasing the glutamate release, reducing the expression of γ-aminobutyric acid, inducing neuroin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 70 publications
2
3
0
Order By: Relevance
“…In addition to shared modules in multiple disorders, we identified disease-specific modules as well, such as the M4 stress module up-regulated in AD and the M5 immunity module up-regulated in epilepsy ( Figure 5 D). These results agree with and promote the awareness that glial cells play an important role in epilepsy, which involves inflammation, oxidative stress, and maladaptive myelination [ 73 , 74 ]. Compared to other diseases, we found that AD is most susceptible to the M4 stress/inflammation module.…”
Section: Resultssupporting
confidence: 89%
“…In addition to shared modules in multiple disorders, we identified disease-specific modules as well, such as the M4 stress module up-regulated in AD and the M5 immunity module up-regulated in epilepsy ( Figure 5 D). These results agree with and promote the awareness that glial cells play an important role in epilepsy, which involves inflammation, oxidative stress, and maladaptive myelination [ 73 , 74 ]. Compared to other diseases, we found that AD is most susceptible to the M4 stress/inflammation module.…”
Section: Resultssupporting
confidence: 89%
“…TNF-α is considered to be the master regulator of pro-inflammatory cytokines and is secreted by reactive microglia and reactive astroglia. TNF-α regulates the neuronal activity by directly affecting the release of glutamate or γ-aminobutyric acid (GABA; Chen et al, 2021). MCP-1 which was also upregulated in DFP exposed animals and mitigated by 1400W in this study, as in our previous study (Putra et al, 2020) implies that the results are reproducible.…”
Section: Discussionsupporting
confidence: 77%
“…IL-17 also activates NF-κB and MAPK signaling pathways [ 77 ], both of which were enriched KEGG pathways. The NF-κB signaling cascade mediates production of pro-inflammatory cytokines, chemokines, and inducible enzymes nitric oxide synthase (iNOS) and COX-2, which all contribute to neuroinflammation [ 78 , 79 , 80 ]. The latter is a protective response by the brain to remove invading pathogens, neutralize noxious stimuli, and initiate tissue repair.…”
Section: Discussionmentioning
confidence: 99%